Implementation of the Kidney Disease Improving Global Outcomes guidelines for the prevention of acute kidney injury after cardiac surgery: An international cohort survey. Issue 6 (12th June 2023) - Massoth, Christina; Küllmar, Mira; Moncho, Azucena Pajares; Suárez, Susana González; Grigoryev, Evgeny; Ivkin, Artem; von Dossow, Vera; Ott, Sascha; Rau, Nadine; Meersch, Melanie; Zarbock, Alexander
Abstract : BACKGROUND: Increasing evidence from randomised controlled trials supports the implementation of a six-measure care bundle proposed by the Kidney Disease Improving Global Outcomes (KDIGO) guidelines in patients at high risk for acute kidney injury (AKI) to reduce its incidence after cardiac surgery. OBJECTIVE: To assess compliance with the KDIGO bundle in clinical practice. DESIGN: Prospective observational multinational study. SETTING: Six international tertiary care centres, from February 2021 to November 2021. PATIENTS: Five hundred and thirty-seven consecutive patients undergoing cardiac surgery during a 1-month observational period. INTERVENTIONS: All patients were assessed for the postoperative implementation of the following measures: avoidance of nephrotoxic medication and radiocontrast agents whenever possible, strict glycaemic control, close monitoring of renal function, optimisation of haemodynamic and volume status and functional monitoring of haemodynamic status. MAIN OUTCOME MEASURES: The primary endpoint was the proportion of patients receiving fully compliant care. Secondary outcomes were occurrence of AKI and major adverse kidney event rate at day 30. RESULTS: The full care bundle was applied to 0.4% of patients. There was avoidance of nephrotoxic drugs in 15.6%, radiocontrast agents in 95.3% and hyperglycaemia in 39.6%. Close monitoring of urine output and serum creatinine was achieved in 6.3%, 57.4% underwent optimisation of volume and haemodynamic status, and 43.9% received functional haemodynamic monitoring. 27.2% developed AKI within 72 h after surgery. The average number of implemented measures was 2.6 ± 1.0 and did not differ between AKI or non-AKI patients ( P  = 0.854). CONCLUSION: Adherence with the KDIGO bundle was very low in cardiac surgery patients. Initiatives to improve guideline compliance might provide a strategy to mitigate the burden of AKI. TRIAL REGISTRATION: www.drks.de DRKS00024204.